PENGARUH FAKTOR INDIVIDU DAN FAKTOR PSIKOLOGI PENYULUH TERHADAP KINERJA PENYULUH PERTANIAN LAPANGAN (PPL) DI KABUPATEN BOYOLALI PROPINSI JAWA TENGAH - Musa Frengkianus Banunaek; Suminah Suminah; Ravik Karsidi (Politeknik Pertanian Negeri Kupang, 2020)
This research aimed to find out the performance of agricultural extension agent, to analyze the effect of the agent’s individual and psychological factors on its performance in undertaking its main duty and to find an empowerment model to improve the performance of agricultural extension agent (thereafter called the agent). The data analysis in this research was conducted using a multiple regression analysis. The result of research showed that the performance of agricultural extension agent belonged to high category (77.78%). Individual and psychological factors of the agent simultaneously affected the performance of it with f statistic value of 1355. The factors affecting positively and significantly the agent’s performance level were: individual factor in the form of experience and psychological factor consisting of the agent’s perception on the agricultural extension profession, attitude and motivation.